2013
DOI: 10.1128/mbio.00451-13
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cyclic di-GMP-Modulating Output Domains in Cyanobacteria: an Illuminating Perspective

Abstract: Microorganisms use a variety of metabolites to respond to external stimuli, including second messengers that amplify primary signals and elicit biochemical changes in a cell. Levels of the second messenger cyclic dimeric GMP (c-di-GMP) are regulated by a variety of environmental stimuli and play a critical role in regulating cellular processes such as biofilm formation and cellular motility. Cyclic di-GMP signaling systems have been largely characterized in pathogenic bacteria; however, proteins that can impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 75 publications
0
75
0
Order By: Relevance
“…After demonstrating that c‐di‐GMP can trigger biofilm formation and aggregation, we hypothesized that BL‐grown WT Synechocystis cells exhibiting high c‐di‐GMP levels could produce biofilm and cells could aggregate. Previously, we showed that c‐di‐GMP levels in Synechocystis are three times higher under BL compared to WL and red light (RL), and almost twice as much when compared to cells under green light (GL) (Agostoni et al, ). When maintained under BL, Synechocystis indeed produced biofilm in an adhesive layer on the bottom of flasks and it was easily perceived by eye (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…After demonstrating that c‐di‐GMP can trigger biofilm formation and aggregation, we hypothesized that BL‐grown WT Synechocystis cells exhibiting high c‐di‐GMP levels could produce biofilm and cells could aggregate. Previously, we showed that c‐di‐GMP levels in Synechocystis are three times higher under BL compared to WL and red light (RL), and almost twice as much when compared to cells under green light (GL) (Agostoni et al, ). When maintained under BL, Synechocystis indeed produced biofilm in an adhesive layer on the bottom of flasks and it was easily perceived by eye (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These residues include RXXD, called the primary I-site, which acts to bind c-di-GMP and quell the enzyme’s catalytic activity while bound (Figure 2). The GGDEF domain may exist independently, or it may be fused to a variety of other domains, including PAS, CACHE, CHASE, MASE, and response regulator domains (1, 18, 23). PDEs that break down c-di-GMP come in two varieties.…”
Section: The Components Of C-di-gmp Signalingmentioning
confidence: 99%
“…PCC 6803 genes encoding these domains (16,19). Many of the c-di-GMP synthesis/degradation proteins have been shown to be specifically involved in a particular response pathway, owing to, for example, transcriptional regulation, protein-protein interaction(s), and variation in the binding affinity of c-di-GMP receptors for c-di-GMP (16).…”
Section: Significancementioning
confidence: 99%
“…C-di-GMP is universally found in bacteria, including cyanobacteria, and generally induces sessile multicellular lifestyles and represses motility in these organisms (16). It seems that light is a major factor regulating c-di-GMP signaling (5,8,(17)(18)(19). The GGDEF domain usually synthesizes c-di-GMP via its diguanylate cyclase (DGC) activity (20), whereas the EAL and HD-GYP domains usually degrade c-di-GMP via their phosphodiesterase (PDE) activities (21,22).…”
mentioning
confidence: 99%